Історичні аспекти підготовки фахівців-біологів в Україні в ХІХ ст - Іванців, Оксана; Іванців, Василь; Ivantsiv, Oksana; Ivantsiv, Vasyl (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті проаналізовано конкретно-історичний матеріал, що відображає умови формування професійної підготовки фахівців-біологів у системі розвитку вищої освіти України в ХІХ ст. Розглянуто iсторичнi аспекти розвитку бiологiчних знань в Українi i формування їх у систематичну пiдготовку спецiалiстiв-бiологiв. Осно¬вою пiдготовки бiологiв є сприйняття бiологiчних поглядiв та переконань, якi розвиваються i закрiплюються у процесi формування професійних якостей.The concrete historical material reflecting the conditions of formation of professional training of biology-specialists in the development of higher education in Ukraine in the XIX century is analyzed in the article. The main task of this paper was to investigate the historical features of the of biology-specialists training in the Ukraine in the XIX century. The historical aspects of the development of biological knowledge in the Ukraine and their formation into system training of biology-specialists. The basis of of biology-specialists training is the assimilation of biological opinions and beliefs, developed and reinforced in the course of formation of professional qualities. All these qualities are successfully formed in spite of the limitations of the state universities. Development in biology and teaching biological disciplines are considered in their work. The education system in the Ukraine of the XIX century was characterized by a certain extension of the network of primary schools of different types. And this demanod suppliment of teachers. These specialists were trained in teachers 'seminaries and teachers' institutes. At that time, the Ukraine had two institutes: Gluhov and Kiev. Best training of biologists was carried out in universities. At the end of the XIX century in Ukraine there were universities that prepared biology-specialists: Kharkiv, Kiev, Lviv, Novo¬rossiysk, Chernivtsi.
Historical Aspects of the Biology-Specialists Training in the Ukraine in the Nineteenth Century
Keywords: фахівці-біологи; підготовка; університет; інститут; ХІХ ст.; biology-specialists; training; university; institute; nineteenth century